Maximal Mandibular Movements among Tanzanian Children - Mugonzibwa E.A., Dr. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Aim: To determine the maximal mandibular movements among Tanzanian children.Subjects and Methods: Analysis of archived data from 869 subjects aged 3½ -16 years of whom 51%were girls. The emergence status of the permanent teeth was determined and classified into fourcategories. The study variables were maximal mandibular movement capacity vertically, inlaterotrusion and protrusion.Results: The mean maximum mandibular opening ranged from 43.8 to 55.8 mm between emergencestages of the dentition. The mean values for maximal mandibular movements in laterotrusion andprotrusion ranged between 6.3 mm and 7.9 mm at the lowest and highest emergence stage among girlsand boys. The mean of the maximum mandibular opening for both sexes increased with theemergence stage of the dentition. Conclusion: Sex and emergence stage of the dentition hadsignificant influences on mandibular maximum opening, laterotrusion and protrusion. Similar studieson maximal mandibular movements in different Tanzanian children strata are recommended